The Role of Sharia-Compliant Investment in Promoting MSME Growth in Indonesia: An Integrative Literature Review - Nurul Inayah; Lukman Hakim (SIMFONI: Jurnal Sains dan Sosial Multidisipliner, 2026)
Micro, Small, and Medium Enterprises (MSMEs) hold a strategic position in the Indonesian economy, yet they still face gaps in access to capital, low financial literacy, limited managerial capacity, and uneven technology adoption. This article aims to analyze the role of Islamic (sharia) investment in driving MSME growth through the integration of commercial finance, Islamic social finance, financial technology, and the strengthening of the business ecosystem. The study employs an integrative literature review, examining scientific articles, books, regulations, and official reports from the Financial Services Authority (OJK), Bank Indonesia, BAZNAS, and government bodies. The literature was selected based on its relevance to MSME financing, Islamic microfinance, productive zakat, waqf, financial inclusion, and digitalization. The findings reveal four main pathways of contribution. First, murabahah, mudharabah, musyarakah, ijarah, and salam contracts provide capital alternatives linked to real economic activity. Second, productive zakat, cash waqf, and qard hasan can serve as initial capital and graduation instruments for vulnerable business actors. Third, Islamic fintech expands outreach, lowers transaction costs, and supports digital record-keeping and marketing. Fourth, the success of Islamic investment depends on synergy among regulation, literacy, mentoring, governance, halal certification, and market access. The main obstacles include low sharia financial inclusion, information asymmetry, weak business record-keeping, the dominance of trade-based financing, and the lack of integration between commercial and social finance. This article recommends a staged Islamic investment ecosystem model that aligns instruments with the developmental stage of MSMEs.